2009
DOI: 10.1007/s00586-008-0860-1
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis and spine involvement in fibrous dysplasia of bone

Abstract: Few studies focused on the prevalence of scoliosis and involvement of the spine in patients with fibrous dysplasia (FD) of bone. We examined for FD involvement of the spine and scoliosis in 56 patients affected by FD of bone. Fifty patients were part of a cohort reported in a multicentric study on FD promoted by European Pediatric Orthopedic Society (EPOS) in 1999, and six were new patients. There were 30 females and 26 males (mean age 12.5 years; range 1-42 years). Twenty-three had monostotic FD, 9 polyostoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…The clinical features CFD encompass a broad clinical spectrum depending upon the location and extent of the lesions. These can vary from mild facial asymmetry or a painless "lump" to serious functional deficits owing to progressive expansion of (6). The ocular effects of FD are particularly worrisome.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features CFD encompass a broad clinical spectrum depending upon the location and extent of the lesions. These can vary from mild facial asymmetry or a painless "lump" to serious functional deficits owing to progressive expansion of (6). The ocular effects of FD are particularly worrisome.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic fracture of the spine is rare [24,33], and there has been only one case report of spinal cord compression from monostotic fibrous dysplasia [33]. Scoliosis has been shown to result from spine involvement of McCune-Albright syndrome in 41.6% of cases and from polyostotic fibrous dysplasia of the spine in 11.1% of cases, but monostotic fibrous dysplasia has not been associated with scoliosis [23]. Sarcomatous transformation of fibrous dysplasia is rare, with a lifetime risk of 0.5%, although this may be a highend estimate given many cases of fibrous dysplasia may remain asymptomatic; the most commonly developed sarcoma is osteosarcoma, followed by fibrosarcoma [10].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…The mean age at presentation for all forms of fibrous dysplasia is 10 years, but the less severe, monostotic form can present later in adulthood [3,10]. Mancini et al reported monostotic fibrous dysplasia presented at a mean age of 16.9 years (range, 7-42 years) [23].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…Vertebral involvement also may occur and result in scoliosis. 87 Patients with McCuneAlbright syndrome are the most severely affected compared with patients with fibrous dysplasia without endocrine abnormalities; they present at an earlier age, lesions tend to be larger, more persistent and cause more complications. 84 The ''café au lait'' skin pigmentations that are characteristic of this disease are distributed over the trunk or proximal parts of the extremities.…”
Section: Clinical Featuresmentioning
confidence: 99%